Interactive high fidelity visualization of complex materials on the GPU - Silva, Nuno Alexandre Campos Pereira da (2013)
Documento submetido para revisão pelos pares. A publicar em Computers & Graphics. ISSN 0097-8493. 37:7 (nov. 2013) p. 809–819